2016
DOI: 10.12972/kjhst.20160027
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Ethylene and Fruit Quality Attributes during Storage in New Apple Cultivars

Abstract: Physiological characteristics of five new apple cultivars from the Korean apple breeding program were evaluated as a function of harvest time and storage after harvest. Internal ethylene concentration (IEC), flesh firmness, soluble solids concentration (SSC), and titratable acidity (TA) were measured in 'Summer Dream', 'Summer King', 'Green Ball', 'Picnic', and 'Hwangok' apples at harvest, during shelf life at 20°C, and one day after cold storage at 0.5°C in air. IEC increased during shelf life in 'Summer Drea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
4
9
0
1
Order By: Relevance
“…Meanwhile, the firmness decreasing level of "Golden Delicious" was severe than that of "Fuji" apple during the entire storage period, which was consistent with the reports made by Win et al (2019) and Yoo et al (2016) that low ethylene production was linked to less reduction of firmness.…”
Section: F I G U R Esupporting
confidence: 89%
See 2 more Smart Citations
“…Meanwhile, the firmness decreasing level of "Golden Delicious" was severe than that of "Fuji" apple during the entire storage period, which was consistent with the reports made by Win et al (2019) and Yoo et al (2016) that low ethylene production was linked to less reduction of firmness.…”
Section: F I G U R Esupporting
confidence: 89%
“…Red (positive) and blue (negative) correlations between analyses of respective values at *p < .05, **p < .01. The numbers in the boxes represented the correlation coefficients This was similar to observations made in other studies (Gwanpua et al, 2013;Johnston et al, 2001;Win et al, 2019;Yoo et al 2016) where ethylene had negative correlation with firmness. In addition, the ethylene production found in "Golden Delicious" was higher than that of "Fuji" apple.…”
Section: F I G U R Esupporting
confidence: 83%
See 1 more Smart Citation
“…In addition, 1-MCP significantly suppressed the IEC in both cultivars, which is mainly involved in fruit ripening, but the IEC observed in ‘Summer King’ apples was higher than that of ‘Green Ball’ apples. This discrepancy could be due to the difference between the concentration of IEC induced by the two different cultivars (Jung and Watkins, 2014; Yoo et al, 2016). Yoo et al (2016) reported that low IEC is linked to less reduction of firmness, as observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy could be due to the difference between the concentration of IEC induced by the two different cultivars (Jung and Watkins, 2014; Yoo et al, 2016). Yoo et al (2016) reported that low IEC is linked to less reduction of firmness, as observed in this study.…”
Section: Discussionmentioning
confidence: 99%